Comportment of prosthetic abdominal mesh.: Estudio de la variación producida por la adición de colágeno - Giossa, Walter; Patiño, Tydeo; Ruiz Costa, Darío; Estrada, Daniel; Pose, Juan; Mariño, Ana (Cirugía del Uruguay, 1988)
The variation produced by collagen in the comport• ment of polyester prosthetic mesh located in the rat peritoneal sac is studied. Results at 3, 7, 14, 21 and 28 days are globally and individually compared between a Dacron mesh and a similar one with the addition of collagen.